Bundling information goods under 'breakeven' price - Toshifumi Kuroda (International Telecommunications Society (ITS), 2014)
Bundling under monopoly tends to increase demand and market efficiency, but likely at the expense of transferring consumers' surplus to firms. Public utilities can use this increase in demand to reduce the monthly fee per consumer. To demonstrate it, I conduct a numerical analysis of the effects of bundling under breakeven price regulation for the Japan Broadcasting Corporation. I estimate the willingness-to-pay for broadcasting services and simulate consumer choices under pure bundling and a-la-carte pricing with breakeven price regulation. Comparing pure bundling and a-la-carte pricing of terrestrial television and satellite television, the increase in demand caused by bundling is very slight due to the strong positive correlation of WTPs. However, compared with a-la-carte pricing, consumer welfare increases by 1.7% with bundling of channels and by 28.2% with bundling of genres.
Keywords: L82; L30; D49; 330; Bundling; Public utilities; Policy analysis